Pulse-Current Electrodeposition for Loading Active Material on Nickel Electrodes for Rechargeable Batteries. (12th March 2013) - Becker, M. D.; Garaventta, G. N.; Visintin, A.
Abstract : Although the pulse-current electrodeposition method is a commonly used technique, it has not been widely employed in electrode preparation. This method was applied to sintered nickel electrodes in a nickel salt solution containing additives. The active material that was obtained, nickel hydroxide, was studied using different characterization techniques. Electrodes impregnated with pulse current had higher capacity than those impregnated with continuous current. The active material is homogeneous and compact with optimum loading and good performance during discharge. These characteristics would provide a large amount of energy in a short time due to an increase in the electrode kinetic reaction.